Visual evoked potentials monitoring in a case of transient post-operative visual loss - Capon, Marie (Indian J Anaesth, 2016)
Post-operative visual loss (POVL) is a rare, albeit potentially serious complication of general anaesthesia. This report describes the case of a 54-year-old woman who developed transient POVL after general anaesthesia following a left posterior parietal meningioma surgery in the prone position and discusses the usefulness of visual evoked potentials monitoring in such situations.